Analisis Pengelolaan Air Irigasi Terhadap Tanaman Pangan - Ai Dini Andriani; Sulwan Permana; Anjas Ninda Hantari (Jurnal Konstruksi, 2025)
Water resources and irrigation management can be seen as one of the key components for increasing food security. The purpose of this study was to determine the effect of irrigation water on food crops. The irrigation channel is located in Jamban Sari village, the planting pattern carried out in Bayongbong Village is rice-rice-secondary crops, with a rice field water requirement of 13,058 mm/day, to determine the evapotranspiration value using the Penmant Montheit method, the largest value is 4,442 mm/day, for the largest value of the land preparation period is 13,816 mm/day, the mainstay discharge using the F.J Mock method, the largest value is 5.98 m3/sec, the calculation value is done by determining Q80% and Q90% from the discharge data that has been sorted from the largest to the smallest value. This study aims to determine the effect of the availability of irrigation water on meeting needs in Bayongbong Village.